Because you bear this name : conceptual metaphor and the moral meaning of 1 Peter - Howe, Bonnie. (Biblical Interpretation Series, 2006)
This study uses conceptual metaphor theory and methodology to analyze the cultural logic and symbolic context, moral content and ethical implications of 1 Peter. Conceptual metaphor study helps explain how people generate ethical understandings; it can help us recognize and account for lively moral discourse between the NT and contemporary readers.